Spatiotemporal distributions of Fukushima-derived radionuclides in nearby marine surface sediments - M. Kusakabe; S. Oikawa; H. Takata; J. Misonoo (Biogeosciences, 2013)
Spatiotemporal distributions of anthropogenic radionuclides in marine surface sediments off Miyagi, Fukushima, and Ibaraki Prefectures were analyzed on the basis of data collected during the monitoring program launched by the Japanese Ministry of Education, Sports, Science and Technology in 2011 right after the Fukushima Dai-ichi Nuclear Power Plant accident began. Concentrations of 137Cs in the surface sediments varied spatially by two orders of magnitude, from 1.7 to 580 Bq kg-dry−1, and there was no obvious correlation between 137Cs concentration and the proximity of the sampling location to the accident site. The total inventory of 137Cs accumulated in the upper 3 cm of surface sediments in the monitoring area was estimated to be 3.78 × 1013 Bq, that is, 0.1–2% of the total 137Cs flux from the plant to the ocean as a result of the accident (the percentage depends on the model used to estimate the total flux). The spatial variations of 137Cs concentration and inventory depended on two main factors: the 137Cs concentration in the overlying water during the first several months after the accident and the physical characteristics of the sediments (water content and bulk density). The temporal variations of the concentrations of other anthropogenic radionuclides (90Sr, 95Nb, 110 mAg, 125Sb, 129Te, and 129 mTe) in the sediments were also investigated. Activity ratios of these nuclides to 137Cs suggest that the nuclides themselves were not homogenized before they were removed from seawater to the sediments.